Adoption Of ICT By Basic Education Teachers: A Systematic Review (Journal of Namibian Studies : History Politics Culture, 2024)
The current study seeks to explore the current situation of the adoption of Information and Communication Technologies (ICT) in basic education schools, specifically at the primary level. For this purpose, a systematic review of scientific articles related to the topic published in 2023 was carried out. Three databases were used to find the articles (Scielo, Scopus, ScienceDirect), of which, of the 1169 articles found, 18 were chosen for analysis. examination. The results were obtained that the use of ICT in primary school has mixed effects on academic performance. Its adoption requires conditions such as equity in access to devices and the Internet, development of teaching and student digital skills, curricular adaptations and adequate infrastructure. Otherwise, instead of supporting learning, poor implementation can frustrate the educational community.